JUSTICE MUST BE EARNED, NOT GIVEN: HONORING MAHMUDKHOJA BEHBUDI’S LEGACY AND THE PROCESS OF PERPETUATING HIS HERITAGE IN UZBEKISTAN - Xudoyberdiyev Otabek Zafar o'g'li (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Annotation: This article explores the contemporary efforts in Uzbekistan to commemorate and institutionalize the legacy of Mahmudkhoja Behbudi — one of the most influential figures of the Jadid reformist movement. The study examines how Behbudi's memory is being honored through education, cultural policy, scholarly research, and public initiatives. By analyzing various monuments, memorial events, school programs, and media representations, the article assesses the extent to which Behbudi’s intellectual and national heritage has been preserved, revived, and integrated into the modern nation-building narrative of Uzbekistan. Special attention is given to the symbolism behind these actions and their impact on youth education, historical awareness, and national identity.